Moggallana’s Journey to Another Buddha-field: How a Mahayana Narrative Crept into the Ekottarika Agama (T 125) - Kuan, Tse-fu (Religions of South Asia, 2019)
The Chinese Ekottarika Agama (EA) stands out among the four Pali Nikayas and the corresponding four Chinese Agamas, which are supposed to be collections of early Buddhist texts. My study of anomalies in a sutta of EA reveals that it is a composite of various textual sources. The original translation of this sutta, presumably non-numerical, was merged with a much shorter, numerical sutta in the process of forming the extant sutta. Zhu Fonian was not satisfied with his original translation of EA, which was carried out under difficult circumstances. As time went by, he had access to other Indic sources and Chinese translations, which could have enabled him to improve this translation. On the other hand, he modified part of his translation in such a creative way that it deviates significantly from the Indic original. Thus our sutta incorporated some new elements, including an episode adapted from a passage in Dharmaraksa’s translation of a Mahayana text. Therefore, Moggallana’s travel to the Brahma Heaven in the original translation was turned into a journey to another buddhafield in the revised version. The religious milieu may have prompted Zhu Fonian to draw upon the Mahayana texts, especially those translated by Dharmaraksa, when revising his translation of EA.